The Effect of Digital Service Quality on Customer Loyalty of the Terandam Pawnshop Branch in Padang City with Satisfaction as a Mediation Variable: JEL Classification: G21, M31, O33, L86, D12 - Ory Febrian Samta; Vidyarini Dwita (Pusat Studi Pembangunan dan Pemberdayaan, 2026)
The rapid development of information technology in the Industrial Revolution 4.0 era has transformed financial transaction patterns and accelerated the adoption of digital financial services in Indonesia. However, various technical problems and user complaints indicate that the quality of digital services still needs improvement. This study aims to analyze the effect of digital service quality on customer loyalty with customer satisfaction as a mediating variable at Pegadaian Terandam Branch in Padang City. This study employed a quantitative causal research design. Data were collected from 110 Pegadaian customers who had experience using digital services through questionnaires distributed using purposive sampling techniques. The research variables consisted of digital service quality as the independent variable, customer loyalty as the dependent variable, and customer satisfaction as the mediating variable. Data were analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS) with SmartPLS software. The results show that digital service quality has a positive and significant effect on customer satisfaction and customer loyalty. Customer satisfaction also has a significant positive effect on customer loyalty. Furthermore, customer satisfaction significantly mediates the relationship between digital service quality and customer loyalty. These findings indicate that improving the accessibility, security, responsiveness, and reliability of digital services can enhance customer satisfaction and strengthen loyalty toward Pegadaian. Digital service quality plays a crucial role in building customer loyalty, both directly and indirectly through customer satisfaction. Therefore, improving digital service performance is essential to strengthen customer trust and sustain long-term loyalty in the digital financial service sector.